2021
DOI: 10.3390/su132413726
|View full text |Cite
|
Sign up to set email alerts
|

A Critical-Systematic Review of the Interactions of Biochar with Soils and the Observable Outcomes

Abstract: Biochar research has experienced a significant increase in the recent two decades. It is growing quickly, with hundreds of reviews, including meta-analyses, that have been published reporting diverse effects of biochar on soil properties and plant performance. However, an in-depth synthesis of biochar–soil interactions at the molecular level is not available. For instance, in many meta-analyses, the effects of biochar on soil properties and functions were summarized without focusing on the specificity of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 133 publications
(182 reference statements)
0
4
0
Order By: Relevance
“…Thus, from FTIR results it is interpreted that due to pyrolysis at 450°C temperature thermal degradation of hemicellulose and cellulose have occurred whereas some aromatics functional group related to lignin remain in biochar. This characteristics enables biochar as potential source for soil improvement (Nkoh et al 2021, Kalina et al 2022. Further application of Calotropis biochar could contribute, by cation exchange capacity/complexation/precipitation, to the treatment of soil and waste water pollutants due to the presence of oxygen based functional group and aromatic structure.…”
Section: Ftir Of Biocharmentioning
confidence: 99%
“…Thus, from FTIR results it is interpreted that due to pyrolysis at 450°C temperature thermal degradation of hemicellulose and cellulose have occurred whereas some aromatics functional group related to lignin remain in biochar. This characteristics enables biochar as potential source for soil improvement (Nkoh et al 2021, Kalina et al 2022. Further application of Calotropis biochar could contribute, by cation exchange capacity/complexation/precipitation, to the treatment of soil and waste water pollutants due to the presence of oxygen based functional group and aromatic structure.…”
Section: Ftir Of Biocharmentioning
confidence: 99%
“…While Andosols exhibit a significant pH-buffering ability [47], this research found that biochars (PLBC, DBC) and PL elevated the soil's pH level (refer to Table 2). Biochars are basic substances, and their alkalinity is influenced by the ash content in their raw materials, as well as by their organic and inorganic bases, carbonates, and functional groups [48]. In addition, unstable feedstocks such as manures have a high potential to provide ash content due to their richer concentrations of volatile matter than wood-based biochars [49].…”
Section: Impact Of Biochars and Manures On The Yield Of Red Clover An...mentioning
confidence: 99%
“…Functional groups located on biochar surfaces can retain and provide nutrients for the growth of microorganisms in the soil [146,171]. Biochar is dominated by negatively charged functional groups; therefore, it mostly affects cation retention [172]. However, due to the pH-dependent nature of the surface, it can also contribute to a smaller extent to an anion adsorption [173,174].…”
Section: Chemical Properties Of Biocharmentioning
confidence: 99%